2010
DOI: 10.1523/jneurosci.3112-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Stability and Drift across Periods of Sleep: Premotor Activity Patterns in a Vocal Control Nucleus of Adult Zebra Finches

Abstract: How stable are neural activity patterns compared across periods of sleep? We evaluated this question in adult zebra finches, whose premotor neurons in the nucleus robustus arcopallialis (RA) exhibit sequences of bursts during daytime singing that are characterized by precise timing relative to song syllables. Each burst has a highly regulated pattern of spikes. We assessed these spike patterns in singing that occurred before and after periods of sleep. For about half of the neurons, one or more premotor bursts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 66 publications
(92 reference statements)
1
23
0
Order By: Relevance
“…Although this model as proposed by Margoliash and co-workers (774,775) aims to explain developmental song learning, it may account also for song learning and the maintenance of learned songs in adult songbirds. There is evidence for song replay and for systematic changes in RA burst activity patterns across sleep in adult zebra finches as well (969). Interestingly, RA burst activity during sleep in some of these cases appeared to be more similar to that observed during singing after sleep than before sleep, suggesting a kind of "preplay" that occurs during sleep and creates new song features (323).…”
Section: Song Learning In Birdsmentioning
confidence: 99%
“…Although this model as proposed by Margoliash and co-workers (774,775) aims to explain developmental song learning, it may account also for song learning and the maintenance of learned songs in adult songbirds. There is evidence for song replay and for systematic changes in RA burst activity patterns across sleep in adult zebra finches as well (969). Interestingly, RA burst activity during sleep in some of these cases appeared to be more similar to that observed during singing after sleep than before sleep, suggesting a kind of "preplay" that occurs during sleep and creates new song features (323).…”
Section: Song Learning In Birdsmentioning
confidence: 99%
“…If sleep replay is a mechanism of memory consolidation, then patterns of neural activity should change across sleep in a manner that is adaptive to learning and memory. Taking advantage of the reliability of RA activity during singing, a recent study reported systematic changes in the bursting properties of individual neurons that were recorded during singing and that were maintained across periods of sleep (Rauske et al 2010). The structure of 33 of 115 bursts (28.7 %) changed across sleep.…”
Section: Sleep and Adult Song Maintenance In Zebra Finchesmentioning
confidence: 99%
“…The effect of sleep on song learning has been shown both at the behavioral (Deregnaucourt et al, 2005) and neural levels (Shank and Margoliash, 2009; Rauske et al, 2010) at different stages of vocal development. In addition, the replay of premotor activity patterns during sleep observed in song control nuclei such as HVC and RA (Chi et al, 2003; Shank and Margoliash, 2009) suggests a possible neural correlate of sleep-related vocal learning processes.…”
Section: The Role Of Nif In Song Learning and Maintenancementioning
confidence: 99%